EFFECT OF TRUNK MOTOR CONTROL TRAINING ON HIP MUSCLES IN ELITE FOOTBALL PLAYERS. Issue 7 (11th March 2014) - Mendis, D; Stanton, W; Hides, J
Abstract : Background: Decreased size and altered function of lumbo-pelvic muscles has been found in elite athletes with low back pain (LBP). Previous research has shown that training trunk neuromotor control in elite football players with and without LBP improved the size and function of muscles important in stability of the lumbo-pelvic region. Hip muscles also contribute to lumbo-pelvic stability and imbalances in these muscles have been associated with LBP in collegiate athletes. Objective: To investigate if a motor control intervention program targeting trunk muscles affects hip muscle size in elite football players with and without LBP. Design: The trial was delivered as a stepped-wedge design with 3 treatment arms: 15 weeks intervention, 8 weeks intervention and a wait-list control who received 7 weeks intervention toward the end of the playing season. Setting: Elite level football club in the National Australian Football League (AFL). Participants: Complete training squad of 46 elite players from an AFL club. Interventions: The motor control program, delivered over the playing season, involved performance of voluntary contractions of the trunk muscles with feedback from ultrasound imaging. Main outcome measurements: Cross-sectional areas of the iliacus, psoas, iliopsoas, sartorius, gluteus minimus, gluteus medius and upper gluteus maximus muscles were measured from magnetic resonance images. Results: The motor control training program was associated with an increase in hip muscle size especially for those with LBP (P<.01). Conclusions: The motor control training program, which targeted proximal muscles of the lumbar spine, had an effect on both trunk and hip muscles. Neuromuscular control training programs may benefit more muscles in the kinetic chain than trunk muscles alone. This finding may be due to the functional components of the motor control program that encouraged optimal trunk and femoro-pelvic alignment when load was added in functional weight bearing positions.